Educational equality in China: analysing educational policies for migrant children in Beijing. Issue 2 (15th March 2017) - Liu, Shuiyun; Liu, Fuxing; Yu, Yafeng
Abstract: This paper focuses on the education of migrant children in Beijing. As of the late 1990s, the Chinese Government has developed several policies to address educational issues among migrant children. The present study analyses data from interviews with key education personnel in Beijing to explore the outcomes of the implementation of such migrant children's education (MCE) policies and the reasons for variation from policy design. The data suggest that there is poorer equality in terms of education among migrant vs. local children than the government has reported. Migrant children are faced with numerous strict admission procedures for public schools. The Chinese Government has not prioritised educational equality, despite professing to do so. The capability and motivation of local institutions for policy implementation are less adequate than might be expected. Using Honig's model of policy implementation, this research shows that the outcomes of the MCE policies are a product of interaction between policy design, participants and implementation context.